DL-assisted programmable multilayer network application awareness system for IP-over-EON - Zuqing ZHU; Jiawei KONG; Bin NIU; Shaofei TANG; Hongqiang FANG; Siqi LIU (Tongxin xuebao)
In order to realize real-time and fine-granularity network monitoring and adjustment,and satisfy the specific QoS demands of various applications,a deep learning (DL) assisted programmable multilayer network application performance awareness system for IP-over-EON was proposed.The distributed network monitoring based on network application performance awareness was combined with centralized network management.The multilayer and fine-grained network monitoring was implemented by distributed network monitoring,and the data analysis through DL was performed.Experimental results indicate that by combining distributed and centralized processing seamlessly,the proposed network monitoring system can not only realize timely and automatic network control and management but also provide superior scalability.